2020
DOI: 10.1055/a-1237-4268
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and In Vivo Immunomodulatory Activity of Physalis angulata Concentrated Ethanolic Extract

Abstract: The need for new immunomodulatory drugs is due to the side effects associated with the prolonged use of the currently used immunomodulatory drugs. In this context, the present work aimed to investigate the immunomodulatory effect of an ethanolic concentrated extract from Physalis angulata. The cytotoxicity of samples was determined using peritoneal macrophages though the Alamar Blue assay. The immunomodulatory activity of the ethanolic extract from P. angulata on activated macrophages was determined by measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…BALB/c mice (males; 6–8 weeks old) were divided into six experimental groups ( n = 6) and treated orally with solidagenone (30, 60, or 90 mg/kg), dexamethasone (30 mg/kg), or vehicle (saline solution with 10% DMSO) 24 and 1 h before the challenge. Subsequently, the animals were challenged through an intraperitoneal injection of 250 μL of carrageenan (Sigma-Aldrich, St. Louis, MO, USA; 1 mg/mL; 250 μL), as previously described [ 39 ]. After 4 h, the mice were euthanized and peritoneal exudates were harvested by peritoneal lavage using a saline solution.…”
Section: Methodsmentioning
confidence: 99%
“…BALB/c mice (males; 6–8 weeks old) were divided into six experimental groups ( n = 6) and treated orally with solidagenone (30, 60, or 90 mg/kg), dexamethasone (30 mg/kg), or vehicle (saline solution with 10% DMSO) 24 and 1 h before the challenge. Subsequently, the animals were challenged through an intraperitoneal injection of 250 μL of carrageenan (Sigma-Aldrich, St. Louis, MO, USA; 1 mg/mL; 250 μL), as previously described [ 39 ]. After 4 h, the mice were euthanized and peritoneal exudates were harvested by peritoneal lavage using a saline solution.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, chemical synthesis to obtain physalins needs to be better explored, since the purification of physalins from natural sources is a time-consuming, costly and not environmentally friendly process that results in a low yield. Due to the fast growth of the plants, which are annual herbs, an approach that has been investigated is the use of a physalis extract concentrated in the physalins, which has shown both low toxicity as well as pharmacological effects ( Nogueira et al, 2013 ; Meira et al, 2015 ; Daltro et al, 2020 ; Do Espírito Santo et al, 2021 ).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…P. angulata has high potential medicinal value and a very long history of being used in traditional medicines around the world. Recent phytochemical and pharmacological studies have confirmed that P. angulata is rich in vitamins, minerals, antioxidants, and many important pharmacologically active constituents, including antibacterial, anti-inflammatory, and anticancer ingredients [3][4][5][6]. In many countries, such as China, Indonesia, Peru, Mexico, and Brazil, P. angulata is often used to treat a variety of illnesses, including dermatitis, tracheitis, impaludism, rheumatism, hepatitis, and analogous conditions [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%